Traditional Chinese Rehabilitation Exercise (TCRE) for Myofascial Pain—A Superficial Synthesis with Missed Opportunities [Letter] - Zhou Z; Liu Q (Journal of Pain Research)
Zhidong Zhou, Qiang Liu The Third Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310005, People’s Republic of ChinaCorrespondence: Qiang Liu, The Third Affiliated Hospital of Zhejiang Chinese Medical University, No. 219 Moganshan Road, Hangzhou, Zhejiang, People’s Republic of China, Email cookie@dewang.cc